Dopa-modified polyamide-amine dendritic polymer as well as preparation method and application thereof

By combining dopamine with polyamide-amine dendrimers, dopamine-modified polyamide-amine dendrimers are synthesized, which solves the shortcomings of implant materials in preventing infection and promoting bone binding, and realizes implants The long-acting antibacterial and osseous binding effect on the surface significantly improves the clinical durability of the implant.

CN119431774AActive Publication Date: 2025-02-14LANZHOU UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411145153.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-20
Publication Date
2025-02-14
Estimated Expiration
2044-08-20

AI Technical Summary

Technical Problem

Existing implant materials have shortcomings in preventing infection and promoting osseous binding, resulting in poor long-term stability and durability of implants.

Method used

Dopamine-modified polyamide-amine dendrimer (DA-PAMAM-NH2) was synthesized by combining dopamine (DA) with polyamide-amine dendrimer (PAMAM-NH2) to construct a bisected bisectal Functional coating material, has antibacterial properties and the effect of promoting bone binding.

Benefits of technology

This dual-function coating material can be adsorbed on the implant surface for a long time and stably, maintain good antibacterial properties, promote bone binding, and significantly improve the clinical durability of the implant.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119431774A_ABST
    Figure CN119431774A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a dopamine (DA) modified polyamide-amine type dendritic polymer. The method comprises the steps of carboxylation of amino terminal dopamine, synthesis of carboxylated dopamine with a protecting group, synthesis of a polyamide-amine dendritic polymer modified by the carboxylated dopamine with the protecting group, and synthesis and application of the dopamine modified polyamide-amine dendritic polymer. DA is introduced into the surface of PAMAM-NH2 to synthesize a DA-PAMAM-NH2 novel high polymer material by utilizing the firm adhesion performance of DA in a humid marine environment and the antibacterial performance and induced osteogenesis performance of a PAMAM-NH2 cationic polymer, the long-acting antibacterial and induced osteogenesis effects of the system as the implant surface bifunctional coating are detected, and the application prospect is wide. And evaluating the effect of the system on the aspect of improving the clinical durability of the implant.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer material synthesis, and in particular relates to a preparation method and application of a DOPA-modified polyamide-amine type dendrimer polymer composite material. Background Art

[0002] With the improvement of medical level, implant materials have been widely used in dental and orthopedic surgery. Compared with traditional restoration technology (fixed dentures, removable dentures), it has the advantages of not damaging adjacent teeth, strong load function, high comfort, etc., and is accepted by the majority of patients. The key factor for the successful restoration of implants is the formation of interface bone between the implant and the bone. Titanium has been widely used as an implant material in orthopedics and dentistry due to its excellent biocompatibility and mechanical properties matching bone tissue.

[0003] However, despite strict surgical disinfection and preventive systemic antibiotic use, implant infection caused by bacteria is still an important factor leading to implant failure. Many studies have been devoted to solving the problem of implant-related infection from different levels. It was found that constructing an antibacterial coating on the surface of the implant to inhibit bacterial growth is a directional strategy for preventing implant infection. However, the current antibacterial coating generally has a too fast release rate and cannot maintain an effective antibacterial concentration locally, making it difficult to achieve the purpose of long-term antibacterial. At the same time, due to the chemical inertness of the titanium implant surface and poor bonding with the surrounding bone tissue, it is difficult to ensure the stability of the implant in the early stage of implantation. Traditional surface modification methods can rarely achieve dual functions at the same time. Secondly, these methods still need to be studied to improve the clinical durability of implants.

[0004] In summary, to improve the long-term success rate of implants, on the one hand, it is necessary to strengthen the antibacterial properties of implants to prevent the occurrence of peri-implant infection, and on the other hand, it is necessary to enhance the bonding performance between implants and surrounding bone tissue to improve the long-term stability of implants. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a dopamine-modified polyamide-amine type dendrimer and its preparation method and application in view of the deficiencies of the above-mentioned prior art. Inspired by mussel foot protein, the present invention intends to optimize and screen out DA with specific adsorption of implants from mussel protein, and introduce it into PAMAM-NH2 to synthesize a new polymer material DA-PAMAM-NH2. By utilizing the specific adsorption performance of DA and the antibacterial and osteoinductive properties of PAMAM-NH2, a dual-functional in vivo implant coating material that can exert long-term antibacterial properties and promote bone bonding is intended to be constructed, providing new strategies and new ideas for improving the long-term stability of implants.

[0006] The technical solution adopted by the present invention is: a dopamine-modified polyamide-amine dendritic polymer, the structural formula of the dopamine-modified polyamide-amine dendritic polymer is:

[0007]

[0008] Wherein, in the above structural formula, n is the number of grafted dopamine, n=4-5.

[0009] The present invention also provides a method for preparing the above-mentioned dopamine-modified polyamidoamine dendritic polymer, which comprises:

[0010] S1, amino-terminal dopamine carboxylation:

[0011] Under the conditions of room temperature and normal pressure, dopamine is dissolved in pyridine, and then succinic anhydride and 4-dimethylaminopyridine (DMAP) are added, stirred and dissolved, reacted for 6 hours, and then the reaction solution is poured into ice ether for precipitation for 2 hours, the product is collected by filtration, and vacuum dried to obtain carboxylated dopamine; the structural formula of the carboxylated dopamine is

[0012]

[0013] S2. Synthesis of carboxylated dopamine with protective groups:

[0014] At 0°C, triethylamine, p-toluenesulfonyl chloride, DMAP and CH2Cl were added to the carboxylated dopamine obtained in S1, and the mixture was reacted at 0°C for 6 h to obtain OTs (p-toluenesulfonyl) protected carboxylated dopamine, the structural formula of which is

[0015]

[0016] S3. Synthesis of polyamidoamine dendrimers modified with carboxylated dopamine with protective groups

[0017] Under room temperature and light-proof conditions, the fifth generation polyamide-amine dendritic polymer is dissolved in methanol, stirred and dissolved, and then Carter condensation agent (BOP) and OTs-protected carboxylated dopamine obtained in S2 are added, stirred and dissolved, and reacted at room temperature for 2 hours to obtain a reaction solution of a polyamide-amine dendritic polymer modified with carboxylated dopamine with a protective group. The structural formula of the polyamide-amine dendritic polymer modified with carboxylated dopamine with a protective group is

[0018]

[0019] S4. Synthesis of dopamine-modified polyamidoamine dendrimers:

[0020] Under nitrogen protection, potassium tert-butoxide was added dropwise to the reaction solution obtained in S3, and then poured into acetone, sealed and protected from light at room temperature, precipitated overnight, and the crude product was collected by filtration. The crude product was then dissolved in dimethyl sulfoxide (DMSO) and fully dissolved, and transferred to a dialysis bag, dialyzed for 24 hours, and the dialysate was collected and freeze-dried to obtain a dopamine-modified polyamide-amine dendrimer with the structural formula:

[0021]

[0022] Preferably, the dosage ratio of dopamine, pyridine, succinic anhydride and DMAP in S1 is 50 mg: 2 mL: 39.20 mg: 3.99 mg.

[0023] Preferably, the equivalent ratio of triethylamine to DMAP in S2 is 60:1.

[0024] Preferably, the usage ratio of the fifth-generation polyamide-amine dendrimer, methanol, BOP and OTs-protected carboxylated dopamine in S3 is 50 mg:2 mL:1.54 mg:2.66 mg; the equivalent ratio of BOP in S3 to the carboxylated dopamine in S2 is 1:5.

[0025] Preferably, the molecular weight cut-off of the dialysis bag in S4 is 8000-14000 DA.

[0026] Preferably, the preparation method of the fifth generation polyamide-amine type dendritic polymer in S3 is:

[0027] Synthesis of S301, G 0.5PAMAM-NH2

[0028] Under the condition of ice bath and nitrogen, methyl acrylate was dissolved in methanol, and then ethylenediamine was added, and the reaction was terminated after stirring at a speed of 1000 r / min for 48 hours under the condition of light protection, and then the dissolved and part of the reaction residues were removed by reduced pressure distillation to obtain the reaction product G 0.5PAMAM-NH2; the molar ratio of methyl acrylate to methanol was 2.4:1;

[0029] S302, G 1.0 Synthesis of PAMAM-NH2

[0030] In an ice bath and nitrogen, the G 0.5PAMAM-NH2 obtained in S301 was dissolved in methanol solution, and then ethylenediamine was added to the obtained solution at room temperature. The reaction was terminated after stirring at a speed of 1000 r / min for 48 hours under light-proof conditions, and then the dissolved and part of the reaction residues were removed by reduced pressure distillation to obtain a reaction product G1.0PAMAM-NH2; the molar ratio of the G 0.5PAMAM-NH2 to ethylenediamine was 1:25;

[0031] S303, G 5.0 Synthesis of PAMAM-NH2

[0032] Ethylene diamine is added to the G1.0PAMAM-NH2 obtained in S302, and a higher generation of PAMAM-NH2 is prepared through continuous Michael addition reaction and amidation reaction until G 5.0PAMAM-NH2 is synthesized, which is the fifth generation of polyamide-amine type dendrimer.

[0033] Polyamidoamine (PAMAM) is a type of dendritic macromolecule, which consists of a central core, an internal cavity, a rich branching structure and easily modifiable surface functional groups. It has the characteristics of controllable molecular weight, multifunctionality, good solubility and biocompatibility. Experiments have shown that PAMAM-NH2 can induce dentin remineralization as a nucleation template. At the same time, the fifth-generation PAMAM-NH2 has 128 amino groups on its surface. Its amino cations generate electrostatic interactions with anions on the surface of bacteria, causing the bacterial cell membrane to rupture and damage, and the cytoplasm to leak out, thereby causing bacterial death. It is a broad-spectrum antibacterial agent. Mussels are a kind of crustacean marine organisms widely distributed in coastal and offshore areas. Their byssus glands can secrete byssus, and the byssus discs formed by the byssus can fix the mussels on the surfaces of various solid substrates. Mussels secrete special adhesion proteins containing a large amount of catechol compounds 3,4-dihydroxy-l-phenylalanine (DOPA), which can adhere firmly and quickly to almost any substrate surface in a humid environment. There are many biomimetic synthetic polymers rich in DOPA units in nature, such as dopamine (DA), which are inspired by this natural adhesion mechanism and can be regarded as a universal choice for anchoring functional molecules.

[0034] The present invention utilizes the strong adhesion properties of DA in a humid environment, as well as the induced hydroxyapatite deposition and antibacterial effect of PAMAM-NH2 cationic polymer, and introduces DA into the fifth-generation PAMAM-NH2 surface to improve its adhesion properties. The purpose is to construct a DA-PAMAM-NH2 dual-functional coating material, test the ability of this system as a dual-functional coating on the implant surface to improve bone integration, remineralization and long-term antibacterial properties, and evaluate the effect of this system on the durability of the implant.

[0035] The present invention also provides the use of the dopamine-modified polyamide-amine dendritic polymer prepared by the above method. The dopamine-modified polyamide-amine dendritic polymer is used for implant coating, which can inhibit the occurrence of peri-implantitis in the long term, promote bone integration, and has potential value in improving the clinical durability of implants.

[0036] Preferably, the dopamine-modified polyamide-amine dendritic polymer is used as a long-lasting bifunctional coating system firmly adsorbed on the surface of the titanium sheet to improve the antibacterial property of the implant and promote peri-implant bone integration, thereby improving the clinical durability of the implant. Its application will provide a new technology for the effective prevention and treatment of peri-implant inflammation and poor bone integration.

[0037] Compared with the prior art, the present invention has the following advantages:

[0038] 1. The present invention starts from the perspective of bionics, simulates the catechol structure in mussel molecules, which plays a key role in the adhesion performance in water environment, and introduces it into polyamide-amine dendritic macromolecules to obtain a coating system with dual effects. It is expected to prevent and treat the occurrence of peri-implantitis and a series of problems such as poor long-term durability of implants.

[0039] 2. The dopamine-modified polyamide-amine dendritic polymer described in the present invention has a strong adsorption effect on the titanium sheet and can effectively resist the scouring of SBF. Even after being immersed in SBF for four weeks, it can still stably exist on the surface of the titanium sheet, achieving long-term antibacterial effect. At the same time, it can induce new bone deposition and promote bone integration. Therefore, it can be used as a dual-functional material with long-term antibacterial properties on the surface of human implants and promoting bone integration.

[0040] 3. The method of the present invention has low raw material cost, simple preparation process, high reaction purity, can be realized by using conventional raw materials and equipment, and is easy to realize industrial production.

[0041] The present invention is further described in detail below with reference to the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 It is a schematic diagram of the synthesis route of the dopamine-modified polyamidoamine dendrimer (DA-PAMAM-NH2) of the present invention.

[0043] Figure 2 This is the H-NMR spectrum of the dopamine-modified polyamidoamine dendrimer prepared in Example 1.

[0044] Figure 3 This is the infrared spectrum of the dopamine-modified polyamidoamine dendrimer prepared in Example 1.

[0045] Figure 4 These are laser confocal microscopy images of DA-PAMAM-NH2 labeled with fluorescein isothiocyanate after adsorption on the surface of the titanium sheet in Example 2, and of DA-PAMAM-NH2 labeled with fluorescein isothiocyanate after adsorption on the surface of the titanium sheet and after rinsing with SBF (a is before rinsing, b is after rinsing).

[0046] Figure 5 These are infrared spectra of the blank titanium sheet in Example 3 (a), the titanium sheet after DA-PAMAM-NH2 adsorption (b), and the titanium sheet surface after DA-PAMAM-NH2 adsorption and SBF washing (c).

[0047] Figure 6 It is a bar graph of bacterial colony counts on the surfaces of titanium sheets of each group in Example 4.

[0048] Figure 7 It is a bar graph of the ratio of live and dead bacteria in the bacterial biofilm formed on the surface of each group of titanium sheets in Example 5.

[0049] Figure 8 These are scanning electron microscope images, atomic force microscope images and X-ray diffraction images of the hydroxyapatite deposition amount on the surface of each group of titanium sheets in Example 6.

[0050] Fig. 9 It is a bar graph of cell adhesion density on the surface of titanium sheets of each group after 1, 3 and 7 days of incubation, respectively, in Example 7.

[0051] Fig.10 It is a bar graph of the expression level of alkaline phosphatase on the surface of titanium sheets of each group after 3 days and 7 days of incubation in Example 8.

[0052] Fig.11 This is a CCK-8 graph of DA-PAMAM-NH2 prepared in Example 9 on mouse preosteoblasts (MC3T3-E1). DETAILED DESCRIPTION

[0053] Example 1

[0054] The DOPA-modified polyamidoamine dendrimer of this embodiment has the structural formula of:

[0055]

[0056] Wherein, in the above structural formula, n is the number of grafted dopamine, n=4-5.

[0057] This embodiment also provides a method for preparing the above-mentioned DOPA-modified polyamidoamine dendrimer. The synthetic route is as follows: Figure 1 As shown, the method is:

[0058] S1, amino terminal dopamine carboxylation:

[0059] Under room temperature and normal pressure, 50 mg of dopamine was dissolved in 2 mL of pyridine, and then 39.20 mg of succinic anhydride and 3.99 mg of 4-dimethylaminopyridine (DMAP) were added. After stirring and dissolving, the reaction was carried out for 6 hours. Then, the reaction solution was poured into 10 mL of ice ether for precipitation for 2 hours. The product was collected by filtration and vacuum dried to obtain carboxylated dopamine. The structural formula of the carboxylated dopamine is

[0060]

[0061] S2. Synthesis of carboxylated dopamine with protective groups:

[0062] At 0°C, triethylamine (Et3N), p-toluenesulfonyl chloride (PTSC) as a protective agent, 4-dimethylaminopyridine (DMAP) as a catalyst and 300 mL CH2Cl as a solvent were added to the carboxylated dopamine (DA-COOH) obtained in S1, and the mixture was reacted at 0°C for 6 h; the equivalent ratio of triethylamine to DMAP was 60:1, and p-toluenesulfonyl (OTs) protected carboxylated dopamine was obtained, the structural formula of which is

[0063]

[0064] S3. Synthesis of polyamidoamine dendrimer modified with carboxylated dopamine with protective groups:

[0065] At room temperature and in the dark, 50 mg of the fifth generation polyamide-amine dendritic polymer was dissolved in 2 mL of methanol, stirred and dissolved, and then 1.54 mg of Carter condensation agent (BOP) and 2.66 mg of OTs-protected carboxylated dopamine obtained in S2 were added, the equivalent ratio of BOP:DA-COOH was 1:5, stirred and dissolved, and reacted at room temperature for 2 h to obtain a reaction solution of a polyamide-amine dendritic polymer modified with carboxylated dopamine with a protective group. The structural formula of the polyamide-amine dendritic polymer modified with carboxylated dopamine with a protective group is

[0066]

[0067] S4. Synthesis of carboxylated dopamine-modified polyamidoamine dendrimers:

[0068] Under nitrogen protection, potassium tert-butoxide (6.0 eq) was added dropwise to the reaction solution obtained in S3, and then poured into 10 mL of acetone, sealed and protected from light at room temperature, precipitated overnight, and the crude product was collected by filtration. The crude product was then dissolved in 1 mL of DMSO and fully dissolved, and transferred to a dialysis bag (molecular weight cutoff of 8000-14000 DA), dialyzed for 24 h, and the dialysate was collected and freeze-dried to obtain a dopamine-modified polyamide-amine dendrimer, denoted as DA-PAMAM-NH2, with a structural formula of

[0069]

[0070] The preparation method of the fifth generation polyamide-amine type dendritic polymer is:

[0071] Synthesis of S301, G 0.5PAMAM-NH2

[0072] Under the condition of ice bath and nitrogen, methyl acrylate was dissolved in methanol, and then ethylenediamine was added, and the reaction was terminated after stirring at a speed of 1000 r / min for 48 hours under the condition of light protection, and then the dissolved and part of the reaction residues were removed by reduced pressure distillation to obtain the reaction product G 0.5PAMAM-NH2; the molar ratio of methyl acrylate to methanol was 2.4:1;

[0073] S302, G 1.0 Synthesis of PAMAM-NH2

[0074] In an ice bath and nitrogen, the G 0.5PAMAM-NH2 obtained in S301 was dissolved in methanol solution, and then ethylenediamine was added to the obtained solution at room temperature. The reaction was terminated after stirring at a speed of 1000 r / min for 48 hours under light-proof conditions, and then the dissolved and part of the reaction residues were removed by reduced pressure distillation to obtain a reaction product G1.0PAMAM-NH2; the molar ratio of the G 0.5PAMAM-NH2 to ethylenediamine was 1:25;

[0075] S303, G 5.0 Synthesis of PAMAM-NH2

[0076] Add ethylenediamine to the G1.0PAMAM-NH2 obtained in S302, and prepare a higher generation PAMAM-NH2 through continuous Michael addition reaction and amidation reaction until G 5.0PAMAM-NH2 is synthesized, which is the fifth generation polyamidoamine dendrimer;

[0077] The dopamine-modified polyamidoamine dendrimer (DA-PAMAM-NH2) prepared in this example is characterized as follows: Figure 2 (H NMR spectrum) and Figure 3(Infrared spectrum) As shown in the figure. The characteristic peaks observed by consulting the literature and comparing with the standard peaks are basically consistent, which shows that the fifth generation of dopamine-modified polyamidoamine dendrimers were successfully synthesized.

[0078] Example 2

[0079] In this example, the adsorption of the polyamide-amine dendritic polymer (DA-PAMAM-NH2) with a terminal group modified by a polypeptide on the surface of a titanium sheet was measured. In this example, the titanium sheet has a size of 10 mm×1 mm.

[0080] The DA-PAMAM-NH2 prepared in Example 1 of the present invention was labeled with fluorescein isothiocyanate (FITC). The specific method was as follows: first, DA-PAMAM-NH2 was mixed with an equimolar amount of FITC, and the mixture was sealed and stirred at room temperature in the dark for 24 hours. After filtering, the mixture was dialyzed for 24 hours in a large beaker containing ultrapure water using a dialysis bag with a molecular weight cutoff of 8000-16000 Daltons. The resulting solution was then frozen and dried to obtain FITC-labeled DA-PAMAM-NH2. Subsequently, the FITC-labeled DA-PAMAM-NH2 was prepared into a 10 mg / mL solution with deionized water, and 100 μL was drawn with a pipette and applied to the surface of the titanium sheet. After drying at room temperature, the surface was rinsed three times with SBF solution. The surface fluorescence distribution of the titanium sheet was observed under an inverted confocal microscope (CLSM) before and after rinsing. The results are shown in FIG. Figure 4 As shown, the experimental results show that after washing with SBF solution, a large amount of DA-PAMAM-NH2 is still firmly adsorbed on the surface of the titanium sheet and can resist the elution force of the SBF solution, thereby indicating that the dopamine-modified polyamide-amine type dendritic polymer synthesized in the present invention has a strong adsorption performance on the surface of the titanium sheet.

[0081] Example 3

[0082] In this example, the adsorption of the polyamidoamine dendritic polymer (DA-PAMAM-NH2) with dopamine modified end groups on the surface of a titanium sheet was measured. In this example, the titanium sheet had a size of 10 mm×1 mm.

[0083] The DA-PAMAM-NH2 of the present invention was prepared into a 10 mg / mL solution with deionized water, and 100 μL was applied to the surface of the titanium sheet with a pipette. After drying at room temperature, the surface was rinsed with SBF solution three times. The adsorption was further observed by attenuated total reflection Fourier transform infrared spectroscopy (ATR-FTIR) before and after rinsing. The results are as follows: Figure 5As shown in the figure, the characteristic peak of DA-PAMAM-NH2 still exists even after washing with 1.5X SBF, which indicates that it has a strong adsorption capacity on the titanium sheet surface and is sufficient to resist the scouring of SBF. This provides a strong guarantee for the subsequent application of DA-PAMAM-NH2 in the moist and complex environment of the oral cavity. Experimental results.

[0084] Example 4

[0085] In this example, the instant antibacterial performance of the polyamidoamine dendritic polymer (DA-PAMAM-NH2) with dopamine modified end groups as described in the present invention adsorbed on the surface of the titanium sheet as a coating was quantitatively determined, and at the same time, after immersing it in a 1.5XSBF solution for 4 weeks, it was tested whether it still had antibacterial performance. In this example, the titanium sheet has a size of 10 mm×1 mm.

[0086] The DA-PAMAM-NH2 prepared in Example 1 was prepared into a solution with a concentration of 10 mg / mL using deionized water, and titanium sheets with a specification of 10 mm×1 mm were randomly divided into a control group, an experimental group 1, and an experimental group 2 (three titanium sheets in each group were replicated).

[0087] (1) The preparation operation of the coating is as follows:

[0088] At room temperature, 100 μL of deionized water was dripped onto the surface of the titanium sheet of the control group with a pipette, and the solution was naturally air-dried in the air; a 10 mg / mL PAMAM-NH2 aqueous solution was dripped onto the surface of the titanium sheet of experimental group 1, and the solution was naturally air-dried in the air, and then the unabsorbed substances on the surface of the titanium sheet were washed with 1.5X SBF; similarly, a 10 mg / mL DA-PAMAM-NH aqueous solution was dripped onto the surface of the titanium sheet of experimental group 2 at room temperature, and the solution was dried in the air, and then the unabsorbed substances on the surface were washed with 1.5X SBF, and then the titanium sheets of experimental group 2 were immersed in 1.5X SBF, stored at a constant temperature of 37°C, and the liquid was replaced every 2 days. After immersion for 4 weeks, the sheets were taken out, washed with 1.5X SBF again, and naturally air-dried at room temperature for use.

[0089] (2) Cultivation of bacterial biofilm and detection of the inhibitory effect of each experimental group on bacterial biofilm:

[0090] In the present invention, Staphylococcus aureus (S.aureus) and Escherichia coli (E.coli) are selected as characteristic bacteria and cultured with BHI culture medium for later use. Each group of titanium sheet samples is placed in a 24-well plate, with 3 parallel samples of each group of titanium sheets. 1.8mL of BHI culture medium is added to each well, and then 200μL of S.aureus or E.coli bacterial solution is inoculated respectively. After the bacterial suspension is mixed with a pipette, it is placed in a 37°C constant temperature incubator for overnight culture, and a bacterial biofilm can be cultured on the surface of the titanium sheet. Then, PBS is used to rinse the floating bacteria on the surface of the titanium sheet that have not formed a biofilm in the clean bench, and then the titanium sheet cultured with the biofilm is transferred to an EP tube containing 2mL PBS. Ultrasonic vibration is performed for 30 minutes to peel off the bacterial biofilm formed on the surface of the titanium sheet, and the plate is coated on the agar plate by the method of continuous dilution. The colony plate count (CFU) is performed by selecting the appropriate number of colonies. The results are as follows Figure 6 As shown in the figure, after 4 weeks of 1.5X SBF immersion and flushing, the bacterial survival rate on the titanium sheet treated with DA-PAMAM-NH2 coating was not statistically different from that before immersion, and the bacteria were mainly dead bacteria, which still maintained good antibacterial properties. This shows that DA-PAMAM-NH2 can be firmly adsorbed on the surface of titanium sheet and exert its antibacterial effect for a long time.

[0091] Example 5

[0092] In this example, the instant antibacterial performance of the polyamidoamine dendritic polymer (DA-PAMAM-NH2) with dopamine modified end groups as described in the present invention adsorbed on the surface of the titanium sheet as a coating was quantitatively determined, and at the same time, after immersing it in a 1.5XSBF solution for 4 weeks, it was tested whether it still had antibacterial performance. In this example, the titanium sheet has a size of 10 mm×1 mm.

[0093] (1) The preparation operation of the coating is as follows:

[0094] At room temperature, 100 μL of deionized water was dripped onto the titanium sheet of the control group using a pipette, and the sheet was naturally air-dried in the air; 100 μL of a 10 mg / mL DA-PAMAM-NH2 aqueous solution was dripped onto the surface of the titanium sheet of experimental group 1, and the sheet was naturally air-dried in the air, and then the unadsorbed substances on the surface of the titanium sheet were washed with 1.5X SBF; similarly, 100 μL of a 10 mg / mL DA-PAMAM-NH2 aqueous solution was dripped onto the surface of the titanium sheet of experimental group 2 at room temperature, and the sheet was naturally air-dried in the air, and then the unadsorbed substances on the surface were washed with 1.5X SBF, and then the titanium sheets of experimental group 2 were immersed in buffer solution 1.5X SBF, stored at a constant temperature of 37°C, and the liquid was replaced every 2 days. After immersion for 4 weeks, the sheets were taken out, washed again with 1.5X SBF, and naturally air-dried at room temperature for use.

[0095] (2) Cultivation of bacterial biofilm and detection of the inhibitory effect of each experimental group on bacterial biofilm

[0096] In the present invention, Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli) are selected as the detection bacteria and cultured with BHI culture medium for standby use. The treated titanium sheets of each experimental group are placed in a 24-well plate, 1.8 mL of BHI culture medium is added to each well, and then 200 μL of Staphylococcus aureus and Escherichia coli bacterial liquids are inoculated respectively. After the bacterial suspension is mixed with a pipette, it is placed in a 37°C constant temperature incubator for overnight culture, and a bacterial biofilm can be cultured on the surface of the titanium sheet. Then, PBS was used to rinse the floating bacteria on the surface of the titanium sheet that had not formed a biofilm in the clean bench, and the sample was allowed to stand at room temperature for several minutes to remove excess moisture from the surface. Then, under light-proof conditions, dye one and dye two were evenly mixed in a 1:1 ratio according to the reagent instructions. Subsequently, 200 μL of dye was added to the surface of each sample using a pipette to ensure that the entire surface of the titanium sheet was coated with the dye. After standing for 25 minutes, excess dye on the sample surface was washed off with PBS buffer, dried at room temperature, and then transferred to a special confocal dish to observe the distribution of live and dead bacteria on the sample surface using CLSM.

[0097] Figure 7 The antimicrobial effect of DA-PAMAM-NH2 through live / dead bacterial staining was demonstrated. In the control group treated with pure water, the biofilm on the titanium sheet surface was mainly composed of live bacteria (S. aureus and E. coli); in contrast, the biofilm on the Ti6Al4V surface treated with PAMAM-NH2 or DA-PAMAM-NH2 was mainly composed of dead bacteria. This is because the amino termini of PAMAM-NH2 or DA-PAMAM-NH2 carry more amino positive charges, which produce electrostatic interactions with the negative charges on the bacterial surface, resulting in cell membrane damage, cytoplasm leakage, and bacterial death. After immersion in 1.5X SBF for 4 weeks, the Ti6Al4V surface treated with PAMAM-NH2 was mainly composed of live bacteria; in contrast, the Ti6Al4V surface treated with DA-PAMAM-NH2 coating was mainly composed of dead bacteria. And there was no significant difference in the ratio of dead bacteria to live bacteria in the DA-PAMAM-NH2 group before and after SBF incubation.

[0098] The experimental results of Example 4 and Example 5 both show that the polyamide-amine dendritic polymer with dopamine-modified terminal groups described in the present invention can be used as a long-acting antibacterial coating material on the surface of dental implants.

[0099] Example 6

[0100] In this example, the adhesion of MC3T3-E1 cells on the surfaces of the titanium sheets treated with the coatings was detected. After 1, 3 and 7 days of incubation, the morphology and adhesion density of the cells on different surfaces were recorded.

[0101] (1) The preparation operation of the coating is as follows:

[0102] The coating preparation method is similar to that in the aforementioned Example 6, except that the titanium sheet substrate is sterilized by high temperature and high pressure and sterilized by ultraviolet irradiation, and each reagent used in the experiment is subjected to bacterial filtration.

[0103] (2) Cell culture and staining

[0104] Mouse preosteoblasts (MC3T3-E1) were obtained from the laboratory of Lanzhou University School of Stomatology. They were cultured in α-MEM medium containing 10% heat-inactivated fetal bovine serum, 100 units / ml penicillin, and 100 mg / ml streptomycin. They were cultured in an incubator (37°C) with 5% CO2 and 95% relative humidity.

[0105] When MC3T3-E1 cells reached 80% confluence, they were cultured at 1.0 × 10 4 The cells were inoculated on the surface of each substrate at a density of 100 / well and cultured in an incubator. The samples were taken out after 1, 3 and 7 days, rinsed twice with PBS buffer, and then fixed with 4% paraformaldehyde fixative. The cells were discarded after 20 minutes, and then permeabilized with 0.5% Triton X-100 for 3 minutes. Finally, the cytoskeleton and cell nucleus were stained with phalloidin and DAPI respectively. After staining, the excess dye was washed off with PBS, and the samples were dried and transferred to a small dish. CLSM was used to observe the cell adhesion. Figure 8 As shown in the figure, after 3 and 7 days of culture, more osteoblasts adhered to the titanium substrate surface treated with DA-PAMAM-NH2 coating compared with the other two groups. This experimental result shows that the titanium sheet coated with DA-PAMAM-NH2 creates a more favorable environment for osteogenesis, and osteoblasts play an important role in the synthesis, secretion and mineralization of bone matrix.

[0106] Example 7

[0107] In this example, the activity of early osteogenic-related protein alkaline phosphatase (ALP) was detected to evaluate the osteogenic differentiation ability of MC3T3-E1 cells on different substrate surfaces. The coating preparation and cell culture method are shown in Example 7.

[0108] When the MC3T3-E1 cells reached 80% confluence, 1.0×10 cells with good growth were selected. 4The surface of each substrate was inoculated at a density of 100 μg / well and cultured in an incubator. After culturing in ordinary α-MEM medium for 1 day, it was replaced with osteogenic induction medium. The formula of osteogenic induction medium was as follows: 10% FBS, 0.1 μmol / L dexamethasone, 50 μmol / L ascorbic acid and 10 μmol / L sodium β-glycerophosphate were added to 250 mL α-MEM medium. The medium was changed every two days, and the ALP expression level was detected after 3d and 7d. The specific method was: discard the original osteogenic induction solution, wash slowly with PBS 3 times, lyse the cells with 100 μL Ripa lysis solution for 30 minutes, obtain cell lysate, use a micro BCA protein detection kit to detect the total protein content in the cell lysate against the standard curve, and then use the ALP activity detection kit to detect the corresponding ALP activity.

[0109] The osteogenic potential of MC3T3-E1 cells was evaluated by assessing the expression of ALP. Fig. 9 As shown in the figure, the ALP activity of MC3T3-E1 cells grown on the titanium sheet treated with DA-PAMAM-NH2 coating was significantly higher than that of the other two groups at all time periods. Taken together, these results support the hypothesis that DA-PAMAM-NH2 coating promotes the proliferation of MC3T3-E1 cells and their osteogenic differentiation by providing a more favorable microenvironment, thereby enhancing the stability of the implant in the early stage.

[0110] Example 8

[0111] In this example, the osteoinduction ability of the polyamidoamine dendritic polymer (DA-PAMAM-NH2) with dopamine modified end groups as described in the present invention adsorbed on the surface of a titanium sheet as a coating was measured. In this example, the titanium sheet has a size of 10 mm×1 mm.

[0112] (1) The preparation operation of the coating is as follows:

[0113] At room temperature, use a pipette to drop 100 μL of deionized water on the titanium sheet of the control group and let it air dry naturally in the air; drop 100 μL of a 10 mg / mL PAMAM-NH2 aqueous solution on the surface of the titanium sheet of the experimental group 1 and let it air dry naturally in the air; drop 100 μL of a 10 mg / mL PAMAM-NH2 aqueous solution on the surface of the titanium sheet of the experimental group 2 and let it air dry naturally in the air for later use.

[0114] (2) Preparation of 1.5X simulated human body fluid (1.5X SBF): 0.1M NaCl, 4.2mM NaHCO3, 3mM KCl, 1mM K2PO4.3H2O, 1.5mM MgCl2.6H2O, 2.6mM CaCl2 and 0.5mM Na2SO4, 1.5M Tris-HCl to adjust pH to 7.4, stored in a plastic bottle, and stored in a refrigerator at 4°C. The treated titanium pieces of each experimental group were placed in a 24-well plate, three per group, and 2mL of the prepared SBF was added to each well. The titanium pieces were mineralized in a constant temperature shaker at 80r and 37°C for 7 days. The mineralization solution was changed every day. After 7 days, the titanium pieces were taken out at a predetermined time point, and the samples were taken out and rinsed with deionized water 3 times, and then dried naturally at room temperature. The surface morphology of the substrate was observed by scanning electron microscopy (SEM) and atomic force microscopy (AFM), and the phase and orientation of the newly formed hydroxyapatite (HA) crystals on the substrate surface were detected by X-ray diffraction (XRD). Fig.10 As shown in the figure, the SEM results show that the original Ti6Al4V substrate has limited ability to induce calcium and phosphate deposition, which results in the formation of only some small crystals on the surface of the titanium sheet. The Ti6Al4V surface treated with PAMAM-NH2 coating also shows only sparse mineral crystals deposited; in contrast, a large number of mineral crystals were found on the Ti6Al4V surface treated with DA-PAMAM-NH2 coating, and the elemental analysis results confirmed that the calcium-phosphorus (Ca / P) ratio of these mineral crystals was close to the HA Ca / P ratio in normal bone tissue. The AFM calculation analysis and three-dimensional reconstruction results of the sample surface roughness showed that the surface roughness of the titanium sheet treated with DA-PAMAM-NH2 coating was higher than that of the other two groups. The XRD test results after 7 days of mineralization showed that obvious diffraction peaks were found at 2θ=26° and 32° on the titanium surface of DA-PAMAM-NH2 coating, which belonged to the characteristic peaks of HA, which further proved that more HA crystals were deposited on these titanium surfaces.

[0115] Example 9

[0116] In this example, the biosafety of the polyamidoamine dendrimer (DA-PAMAM-NH2) modified with dopamine end groups described in Example 1 as a coating material was studied on mouse preosteoblasts (MC3T3-E1).

[0117] The cytotoxicity of DA-PAMAM-NH2 was determined by cell counting kit-8 (CCK-8). After MC3T3-E1 cells reached 80% confluence, the cells were plated at 1.0×10 4Cells were seeded at a density of 100 μL / well in a 96-well plate and incubated for 24 h. The original culture medium was then replaced with 100 μL of fresh culture medium containing different concentrations of DA-PAMAM-NH2. After overnight incubation, 10 μL of CCK-8 solution was added to each well and incubated in cell culture medium at 37°C for 4 h, after which the absorbance at 570 nm was measured using an ELISA reader.

[0118] Cell viability (%) = ([A] test - [A] blank) / ([A] control - [A] blank) × 100%,

[0119] Where [A] test represents the absorbance of wells containing DA-PAMAM-NH2 solution, cell culture medium and cells; [A] blank represents the absorbance of wells containing culture medium only; [A] control represents the absorbance of wells containing cells and culture medium.

[0120] Calculate the parallel absorbance of 6 wells respectively. The cell viability detection chart of MC3T3-E1 cells is as follows Fig.11 The results showed that when the concentration of DA-PAMAM-NH2 was between 0.625 mg / mL and 20 mg / mL, the relative cell survival rate decreased from 142% at 0.625 mg / mL to about 50% at 20 mg / mL, and with the gradient increase of DA-PAMAM-NH2 concentration, the cell survival rate showed a significant downward trend, especially when the concentration of DA-PAMAM-NH2 was 20 mg / mL, which had a greater impact on cell activity. When the concentration of DA-PAMAM-NH2 was 10 mg / mL, the cell activity remained at about 90%.

[0121] The present invention is inspired by mussel protein and analyzes that the synthesized DA has the ability to be firmly adsorbed on the surface of the implant. It is successfully introduced into the surface of PAMAM-NH2 by chemical synthesis to synthesize a DA-PAMAM-NH2 polymer complex. The introduction of DA enables DA-PAMAM-NH2 to be firmly and durably attached to the surface of the implant, and can effectively resist the scouring of SBF, which is a key factor in ensuring the long-term stability of the implant; in an in vitro environment, the DA-PAMAM-NH2 coating can maintain good antibacterial properties for a long time, and can induce the production of hydroxyapatite crystals, which is beneficial to the adhesion of osteoblasts and promotes bone integration; at the same time, the coating can still maintain good long-term antibacterial properties and induction of osteogenesis in the complex environment of the animal body. Therefore, the application of DA-PAMAM-NH2 dual-functional coating will provide a new technology for the effective prevention and treatment of peri-implant inflammation and poor bone integration.

[0122] The present invention mainly focuses on the research of using dopamine-modified polyamidoamine dendrimer as implant coating to reduce the occurrence of peri-implantitis and promote peri-implant bone integration, thereby improving the clinical durability of implants. The summary is as follows:

[0123] (1) DA, which has strong adsorption capacity inspired by mussel protein, was successfully introduced into the surface of PAMAM-NH2 to synthesize a new dendritic polymer material DA-PAMAM-NH2 with good biocompatibility.

[0124] (2) DA-PAMAM-NH2 can be firmly adsorbed to the surface of titanium sheet and can still maintain strong adsorption capacity in an environment of simulated human body fluid immersion and flushing. This is the key to the long-term effect of this dual-functional coating.

[0125] (3) The DA-PAMAM-NH2 coating exhibited excellent immediate and long-lasting antibacterial properties in vitro, which was attributed to its strong adsorption ability on the surface of titanium sheets. At the same time, the DA-PAMAM-NH2 coating was more likely to induce the formation of new bone on the surface of titanium sheets.

[0126] (4) Titanium implants loaded with DA-PAMAM-NH2 dual-functional coatings exerted the dual effects of long-lasting antibacterial properties and inducing osteogenesis in rat models of concurrent infection and bone defects, significantly reducing the incidence of postoperative implant infection and promoting bone integration around the implant. It has good clinical application potential and provides new technology for improving the clinical life of implants.

[0127] The method of the present invention has low raw material cost, simple preparation process, high reaction purity, can be realized by using conventional raw materials and equipment, and is easy to realize industrial production.

[0128] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A dopamine-modified polyamidoamine dendrimer, characterized in that: The structural formula of the dopamine-modified polyamidoamine dendrimer is: Wherein, in the above structural formula, n is the number of grafted dopamine, n=4-5.

2. A method for preparing the dopamine-modified polyamidoamine dendrimer according to claim 1, characterized in that: The method is: S1, amino-terminal dopamine carboxylation: Under the conditions of room temperature and normal pressure, dopamine is dissolved in pyridine, and then succinic anhydride and 4-dimethylaminopyridine are added, stirred and dissolved, reacted for 6 hours, and then the reaction solution is poured into ice ether for precipitation for 2 hours, the product is collected by filtration, and vacuum dried to obtain carboxylated dopamine; the structural formula of the carboxylated dopamine is: S2. Synthesis of carboxylated dopamine with protective groups: At 0°C, triethylamine, p-toluenesulfonyl chloride, DMAP and CH2Cl were added to the carboxylated dopamine obtained in S1, and the reaction was carried out at 0°C for 6 hours to obtain p-toluenesulfonyl protected carboxylated dopamine, the structural formula of which is: S3. Synthesis of polyamidoamine dendrimers modified with carboxylated dopamine with protective groups At room temperature and in the dark, the fifth generation polyamide-amine dendritic polymer was dissolved in methanol, stirred and dissolved, and then the Carter condensation agent and the OTs-protected carboxylated dopamine obtained in S2 were added, stirred and dissolved, and reacted at room temperature for 2 hours to obtain a reaction solution of a polyamide-amine dendritic polymer modified with carboxylated dopamine with a protective group. The structural formula of the polyamide-amine dendritic polymer modified with carboxylated dopamine with a protective group is: S4. Synthesis of dopamine-modified polyamidoamine dendrimers: Under nitrogen protection, potassium tert-butoxide was added dropwise to the reaction solution obtained in S3, and then poured into acetone, sealed and protected from light at room temperature, precipitated overnight, and the crude product was collected by filtration. The crude product was then dissolved in dimethyl sulfoxide and fully dissolved, and transferred to a dialysis bag, dialyzed for 24 hours, and the dialysate was collected and freeze-dried to obtain a dopamine-modified polyamidoamine dendrimer having the structural formula:

3. The method according to claim 2, characterized in that The dosage ratio of dopamine, pyridine, succinic anhydride and DMAP in S1 is 50 mg: 2 mL: 39.20 mg: 3.99 mg.

4. The method according to claim 2, characterized in that: The equivalent ratio of triethylamine and DMAP in S2 is 60:

1.

5. The method according to claim 2, characterized in that: The usage ratio of the fifth generation polyamide-amine dendrimer, methanol, BOP and OTs-protected carboxylated dopamine described in S3 is 50 mg:2 mL:1.54 mg:2.66 mg, and the equivalent ratio of BOP described in S3 and carboxylated dopamine described in S2 is 1:

5.

6. The method according to claim 2, characterized in that The molecular weight cut-off of the dialysis bag in S4 is 8000-14000 DA.

7. The method according to claim 2, characterized in that: The preparation method of the fifth generation polyamide-amine type dendritic polymer described in S3 is: Synthesis of S301, G 0.5PAMAM-NH2 In an ice bath and nitrogen, methyl acrylate was dissolved in methanol, and then ethylenediamine was added. The mixture was stirred at a speed of 1000 r / min for 48 hours under light-proof conditions to terminate the reaction. The dissolved and part of the reaction residues were removed by reduced pressure distillation to obtain a reaction product G 0.5PAMAM-NH2; the molar ratio of methyl acrylate to methanol was 2.4:1; S302, G 1.0 Synthesis of PAMAM-NH2 In an ice bath and nitrogen, the G0.5PAMAM-NH2 obtained in S301 was dissolved in methanol solution, and then ethylenediamine was added to the obtained solution at room temperature, and the reaction was terminated after stirring at a speed of 1000 r / min for 48 hours under light-proof conditions, and then the dissolved and part of the reaction residues were removed by reduced pressure distillation to obtain a reaction product G1.0PAMAM-NH2; the molar ratio of the G0.5PAMAM-NH2 to ethylenediamine was 1:25; S303, G 5.0 Synthesis of PAMAM-NH2 Ethylene diamine is added to the G1.0PAMAM-NH2 obtained in S302, and a higher generation of PAMAM-NH2 is prepared through continuous Michael addition reaction and amidation reaction until G 5.0PAMAM-NH2 is synthesized, which is the fifth generation of polyamide-amine type dendrimer.

8. Use of a dopamine-modified polyamidoamine dendrimer prepared by the method according to any one of claims 2 to 7, characterized in that: The dopamine-modified polyamide-amine dendrimer is used for implant coating to inhibit the occurrence of peri-implantitis, promote bone integration, and improve the long-term stability of the implant.

9. The use according to claim 8, characterized in that: The dopamine-modified polyamide-amine dendrimer is used as a long-acting dual-functional coating system firmly adsorbed on the surface of a titanium sheet, and is used to improve the antibacterial property of an implant, promote bone bonding around the implant, and improve the clinical durability of the implant.

Citation Information

Patent Citations

  • Polypeptide-modifying polyamide-amine branch type polymer and preparation method and application thereof

    CN106589358A

  • Method for preparing bifunctional polyether-ether-ketone by combining mussel derived peptide with biological orthogonal reaction and application of bifunctional polyether-ether-ketone

    CN113354786A

  • Water-soluble dendrimer complex of poorly soluble bioactive compounds

    KR1020160131921A